Sport-specific characteristics of trunk muscles in collegiate wrestlers and judokas - Iwai, K.; Okada, T.; Nakazato, K.; Fujimoto, H.; Yamamoto, Y.; Nakajima, H. (The Journal of Strength and Conditioning Research, 2008)
This study evaluated the sport-specific characteristics of the cross-sectional areas (CSAs) of trunk muscles and trunk muscle strength in wrestlers and judokas. We also examined whether their trunk muscles and muscle strength depended on athletic performance levels in each sport. The subjects comprised 14 male collegiate wrestlers and 14 judokas. Magnetic resonance imaging was used to assess the trunk muscle CSAs at the L3-4 level parallel to the lumbar disc space. A Biodex System3 was used to measure isokinetic trunk flexor and extensor muscle strength of peak torque, work, average torque, and average power. The absolute and relative CSAs of the trunk muscles in the wrestlers and judokas were significantly different (rectus abdominis: wrestling > judo, P < 0.05; obliques: wrestling < judo, P < 0.05; quadratus lumborum: wrestling < judo, P < 0.01). We confirmed that the absolute and relative trunk extensor and flexor strength of peak torque, work, and average torque were significantly higher in the collegiate wrestlers than in judokas. On athletic performance, the tendency of the CSAs and muscular strength of trunk muscles was not consistent with athletic performance levels in each sport. Our findings indicated that the sport-specific characteristics of the CSAs of the trunk muscles and trunk muscle strength obviously differed between the 2 similar sports. Athletes should practice the sport-specific training of trunk muscles and develop sport specificity in their sports. Particularly, wrestlers have to train in trunk flexion and extension motions, and judokas need to strengthen trunk rotation and lateral flexion motions. This information will be available for athletes as well as strength and technical training coaches in wrestling, judo, and the other sports.